Synergistic effect of bimodal-sized SiCp and a dynamically precipitated Mg17Al12 phase on microstructure and mechanical properties of SiCp/AZ61 composites during hot extrusion process at different extrusion temperatures - Ming Li; Gang Li; Mengling Yao; Dijia Zhao; Jianxin Zhou; Shulin Lü; Yajun Yin; Xiaoyuan Ji; Qiang Chen; Hongxia Wang (Journal of Materials Research and Technology)
To clarify the synergistic effect of bimodally sized (6 vol% micro-sized and 1 vol% nano-sized) SiC particles and a dynamically precipitated Mg17Al12 phase on the microstructure and mechanical properties of SiCp/AZ61 composites during the hot extrusion process, homogenized bimodally sized SiCp/AZ61 composites were extruded at different temperatures (280, 320, and 360 °C). After extrusion, the distribution of SiCp was transformed from a necklace-like arrangement in the as-cast state to a ribbon-like distribution along the direction of extrusion, which was beneficial for stimulating dynamic recrystallization and precipitation nucleation. The size of the dynamically recrystallized grains and the precipitated Mg17Al12 phase, as well as the texture intensity of the composite, gradually increased with an increase in the extrusion temperature, while the fraction of dynamically precipitated Mg17Al12 exhibited the opposite trend. The composite demonstrated optimal tensile strength at an extrusion temperature of 280 °C, characterized by a yield strength (YS) of 260 MPa, an ultimate tensile strength (UTS) of 320 MPa, and an elongation (EL) of 7.4 %. The high strength of the extruded composite was primarily attributed to the synergistic effects of fine-grained strengthening, Orowan strengthening and thermal mismatch strengthening; among these, fine-grained strengthening, and Orowan strengthening played a predominant role.